Compaction and strength characteristics of an expansive clay stabilised with lime sludge and cement - Phanikumar, B.R.; Ramanjaneya Raju, E. (Soils and foundations, 2020)
The chemical stabilization of expansive soils has been found to be quite successful in controlling detrimental volume changes due to swell-shrink behaviour. Lime, cement, CaCl2, fly ash, pond ash and other chemical reagents have been effective in stabilizing expansive soils and improving their characteristics. The influence of lime sludge, a by-product of the paper industry, on the index properties of expansive clays was investigated. Their LL, PI and FSI, and the engineering characteristics of these clays were measured after being treated, including their compaction characteristics, stress-strain behaviours at different curing periods and CBRs. The index and engineering properties of the clay-lime sludge blends were studied for different lime sludge contents. As the compacted density did not show a satisfactory improvement upon addition of lime sludge, 10% cement was added to all the lime sludge-clay blends to study its influence on the above properties of lime sludge–treated expansive clay. The addition of 10% cement resulted in lower LL, PI and FSI and higher densities, strengths and CBRs.